2021
DOI: 10.2196/21819
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in Designing Digital Peer Support for Mental Health: Interview Study Among Users of a Digital Support System (Buddy Project)

Abstract: Background Peer support is an approach to cope with mental illness, and technology provides a way to facilitate peer support. However, there are barriers to seeking support in offline and technology-mediated contexts. Objective This study aims to uncover potential ways to design digital mental health peer support systems and to outline a set of principles for future designers to consider as they embark on designing these systems. By learning how existin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 60 publications
(59 reference statements)
4
27
0
Order By: Relevance
“…Social media helps college students, in general [22], and those who are suffering to attain improved mental well-being, in particular [9,10]. Thus, researchers have identified numerous factors that drive online social support [23] and have proposed computing platforms that would promote online mental health support from peers [17,24]. Despite the demonstrated importance of online social support, researchers have yet to empirically study the motives and challenges behind such support from the perspective of the peers who are expected to provide it.…”
Section: Online Social and Peer Support For Mental Healthmentioning
confidence: 99%
“…Social media helps college students, in general [22], and those who are suffering to attain improved mental well-being, in particular [9,10]. Thus, researchers have identified numerous factors that drive online social support [23] and have proposed computing platforms that would promote online mental health support from peers [17,24]. Despite the demonstrated importance of online social support, researchers have yet to empirically study the motives and challenges behind such support from the perspective of the peers who are expected to provide it.…”
Section: Online Social and Peer Support For Mental Healthmentioning
confidence: 99%
“…However, this heuristic approach is not personalized to the user or context. A substantial body of work has highlighted the need for such personalization as an area for future research in the study of mental health BITs (e.g., [59,71,72,93]), as well as the vital need to incorporate peer supporters [4,24,44,67,68]. Crowdsourcing is thus a second approach that can help to leverage peer support, provide users with personalized reframes, and scale BITs outside of the supervision of professional therapists.…”
Section: 22mentioning
confidence: 99%
“…Other papers focus matching chat partners. For example, Andalibi & Flood interviewed users of Buddy Project, which connects anonymous youths struggling with mental health [4]. Unlike physical illnesses such as cancer [32,51,89] or rare diseases [52], where research has established that matching based on condition is a crucial goal, [4] found that users should be paired based on shared interests or identity, rather than mental health diagnoses, since over-exposure to the same mental illness can lead to unhealthy comparisons or disordered coping mechanisms.…”
Section: Algorithmic Scaffolding For Supportive Messaging and Moderationmentioning
confidence: 99%
See 1 more Smart Citation
“…In automotive industry, emotion recognition coupled with behavioral interventions can help drivers to reduce their stress levels as well as the risk of car accidents [24,25,32]. Emotion recognition has a large range of applicability, being also studied for healthcare delivery [3,19], mental health [26], assistive technologies [33], and games [15].…”
mentioning
confidence: 99%